The Role of Safety Leadership and Safety Knowledge in Improving Safety Performance through Safety Motivation - Fatmah Bagis; Lintang Ramdhani Larasati; Hengky Widhiandono; Alfalisyado (EDUCATION JOURNAL OF INDONESIA, 2025)
This research uses safety motivation as a mediating variable to test the effect of safety leadership and safety knowledge on safety performance. This research uses a quantitative methodology. The population of this study was 235 workers of PT Sumber Segara Primadaya PLTU Cilacap. The non-probability sampling approach was used together with the total sampling strategy, resulting in 235 samples. Partial Least Squares analysis was used as a data analysis method for this study. Analytical calculations at a significance level of 5% showed that safety performance was positively and significantly be affected by safety leadership and safety knowledge. Safety motivation is positively and significantly be affected by safety leadership and safety knowledge, and the safety motivation variable can mediate the relationship between safety performance and safety leadership as well as between safety knowledge and safety performance. Keywords: Safety Leadership, Safety Knowledge, Safety Performance, Safety Motivation